Genome-wide analysis of DGAT gene family in Perilla frutescens and functional characterization of PfDGAT2-2 and PfDGAT3-1 in Arabidopsis - Xu, Huaxiang (Plant science : an international journal of experimental plant biology, 2022)
Copyright © 2022 Elsevier B.V. All rights reserved.